Behavior Analysis and Clustering of Consumers Towards Halal Awareness - Sari, Dewi Intan; Hermadi, Irman; Hasanah , Nur (Journal of Consumer Sciences, 2023)
Due to Indonesia's large Muslim population, the issue of halal is contentious for Indonesians, and many restaurants in Indonesia do not have halal certification. This study investigates the various factors that influence customer behavior and identifies managerially implementable consumer clusters. This study used a quantitative methodology, focusing on a sample of consumers residing in the Greater Jakarta area. Lemeshow sampling was used to gather data from 196 respondents via an online survey. The analysis technique consisted of Structural Equation Modeling (SEM)-Partial Least Square and cluster analysis using the K-means algorithm with the Waikato Environment for Knowledge Analysis (WEKA). Subjective norms, perceived behavioral control, halal awareness, and intention factors have been proven to have positive and significant effects on consumer behavior when choosing a halal restaurant. The findings on consumer clusters that have evolved provide significant managerial implications. Assistance is required from halal institutions, businesses, and consumers with a high level of halal awareness to raise their awareness of halal.